Endothelial to Mesenchymal Transition in the Cardiogenesis and Cardiovascular Diseases - Anbara, Taha; Sharifi, Masuomeh; Aboutaleb, Nahid (Current Cardiology Reviews, 2020)
Today, cardiovascular diseases remain a leading cause of morbidity and mortality worldwide. Endothelial to mesenchymal transition (EndMT) does not only play a major role in the course of development but also contributes to several cardiovascular diseases in adulthood. EndMT is characterized by down-regulation of the endothelial proteins and highly up-regulated fibrotic specific genes and extracellular matrix-forming proteins. EndMT is also a transforming growth factor- β-driven (TGF-β) process in which endothelial cells lose their endothelial characteristics and acquire a mesenchymal phenotype with expression of α-smooth muscle actin (α-SMA), fibroblastspecific protein 1, etc. EndMT is a vital process during cardiac development, thus disrupted EndMT gives rise to the congenital heart diseases, namely septal defects and valve abnormalities. In this review, we have discussed the main signaling pathways and mechanisms participating in the process of EndMT such as TGF-β and Bone morphogenetic protein (BMP), Wnt#, and Notch signaling pathway and also studied the role of EndMT in physiological cardiovascular development and pathological conditions including myocardial infarction, pulmonary arterial hypertension, congenital heart defects, cardiac fibrosis, and atherosclerosis. As a perspective view, having a clear understanding of involving cellular and molecular mechanisms in EndMT and conducting Randomized controlled trials (RCTs) with a large number of samples for involving pharmacological agents may guide us into novel therapeutic approaches of congenital disorders and heart diseases.
Keywords: cardiovascular disease